Implementasi Mobile Commerce Pada Poljamshop - Rama Dhonal; Rezagi Meilano; Febby Nanda Utami; Misyati Misyati (Journal of Applied Accounting and Business, 2022)
Poljamshop is an information system that is used to market products at the Jambi Polytechnic and also collaborating partners. Currently there are only sales through the website and few visitors because they are not known to the public, so sales are still personal through mouth to mouth promotions or social media promotions. With this, e-commerce to help Poljamshop increase customer satisfaction to choose or order a product at Poljamshop. This application is made by developing a system using the waterfall method, the tools used to describe the model of this application system are Context Diagrams, Data Flow Diagrams (DFD) and Entity Relationship Diagrams (ERD). The purpose of this final project is to create a mobile commerce on Poljamshop.